First Report in the presence of Post-Weaning Multisystemic Wasting Syndrome and Porcine Circo virus type 2 in Greece - KYRIAKIS (ΣΠ. Κ. ΚΥΡΙΑΚΗΣ), S. C.; KENNEDY, S.; SAOULIDIS (Κ. ΣΑΟΥΛΙΔΗΣ), K.; LEKKAS (Σ. ΛΕΚΚΑΣ), S.; MILIOTIS (Χ.Κ.ΜΗΛΙΩΤΗΣ), Ch. C.; BALKAMOS (Γ.Κ. ΜΠΑΛΚΑΜΟΣ), G. C.; PAPOUTSIS (Π.Α. ΠΑΠΟΥΤΣΗΣ), P. A. (Journal of the Hellenic Veterinary Medical Society, 2018)
Post-weaning Multisystemic Wasting Syndrome (PMWS) is a new infectious disease of pigs at nursery and growing phase of production. A new strain of porcine circovirus (PCV), PCV type 2, seems to be the cause. The aim of this study was to investigate whether outbreaks of disease with clinical signs similar to those of PMWS, observed in several farms in Greece, were associated to the presence of PCV2. To establish a diagnosis in two pig farms suspected of being positive to PMWS, ten affected pigs were euthanised. The clinical and post-mortem findings in these pigs were highly suggestive of PMWS. Histopathology has revealed interstitial pneumonia and infiltration of mononuclear cells in periportal areas of the liver and in mesenteric lymph nodes. According to previous studies these are characteristic lesions of PMWS. The final diagnosis was confirmed by demonstrating antigens and nucleic acid in PCV2-affected tissues using immunohistochemistry and in situ-hybridisation methods.